FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA BAYI DI KELURAHAN PAYA PASIR KECAMATAN MEDAN MARELAN TAHUN 2023 - Mira Indrayani; Suci Wulandari (Jurnal Ilmiah Kebidanan Imelda, 2024)
Background : _ Exclusive breastfeeding is breast milk given to baby since born for 6 ( six ) months , without food companion except vitamins and immunizations . Objective : Study This aim For know influencing factors _ Mother providing exclusive breast milk to babies in Paya Pasir Village Medan Marelan District 2023. Method : Type of research used da`lam study This is observational analytic with cross sectional approach . Population in study This is all over mother who has baby as well as follow present For follow immunization as well as counseling in Paya Pasir Village Medan Marelan District In 2023 there will be 30 people. Withdrawal sample taken in a way Total Sampling. Testing hypothesis with Chi Square test. Results: From the results study show there is influence significant on the variable knowledge (P=0.003), support husband (P=0.000), officer health (P=0.000), efficacy self (P=0.001), social economics (P=0.000). Conclusion: In research This that There is influence significant knowledge, support husband, officer health, efficacy self and social economy to exclusive breastfeeding for babies. _ Suggestion : Study recommend to officer health For give counseling about exclusive breastfeeding _ to mother who has babies in Paya Pasir Village Medan Marelan District .